2002
DOI: 10.1007/s00420-002-0324-6
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed sleep-wake patterns during and after short-term international travel among academics attending conferences

Abstract: In academics, short-term international travel causes sleep disturbances both during and at home after eastward travel and a delay in the sleep timing at home after westward travel. Although the subjects in this study might be atypical of business travelers, the current data suggest that strategies are needed to facilitate recovery from disturbed sleep-wake patterns at home after travel, i.e., redesign of post-travel work schedules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…However, rhythms in JL cells were not different from those of CTL cells in subsequent weeks (2 nd wk, 3 rd wk), throughout which all cells showed nearly identical rhythmic cycles in luminescence (Fig 1B, 1C and 1D). These effects are similar to those that occur with travel across different time zones, when rhythms are affected in the first week following travel but subsequently adapt to the new, stable environment [24]. A phase delay (8.2 hours) and reduced amplitude of JL cell rhythms were also observed in the first week after a short-term circadian desynchronization schedule of only 6 days (S1 Fig).…”
Section: Resultssupporting
confidence: 70%
“…However, rhythms in JL cells were not different from those of CTL cells in subsequent weeks (2 nd wk, 3 rd wk), throughout which all cells showed nearly identical rhythmic cycles in luminescence (Fig 1B, 1C and 1D). These effects are similar to those that occur with travel across different time zones, when rhythms are affected in the first week following travel but subsequently adapt to the new, stable environment [24]. A phase delay (8.2 hours) and reduced amplitude of JL cell rhythms were also observed in the first week after a short-term circadian desynchronization schedule of only 6 days (S1 Fig).…”
Section: Resultssupporting
confidence: 70%
“…Though this typically occurs when time zones are rapidly crossed during air travel (Waterhouse et al, 2004), symptoms of jet lag have also been noted following simulated time zone changes in the laboratory, highlighting that unlike travel fatigue, jet lag is not caused solely by the demands of travel (Waterhouse et al, 2007). One of the main reported symptoms is poor sleep, especially delayed sleep onset and early awakening after eastward and westward flights, respectively (Beaumont et al, 2004;Takahashi, Nakata, & Arito, 2002). It is proposed that symptoms are worse the greater the number of time zones crossed and if travelling east rather than west (Waterhouse et al, 2004).…”
Section: Jet Lagmentioning
confidence: 99%
“…Whilst evidence suggests these devices may adjust circadian rhythms in well controlled laboratory studies (Wright, Lack, & Kennaway, 2004), their effectiveness at enhancing the recovery of physical performance following transmeridian air travel is limited (Boulos et al, 2002), particularly in elite team sport athletes (Thompson et al, 2013). Furthermore, as sleep disruption is likely during and following long-haul transmeridian air travel (Beaumont et al, 2004;Takahashi et al, 2002;Waterhouse et al, 2002), which may itself reduce ensuing physical performance, sleep interventions that minimise this disruption may also enhance performance recovery, though this remains to be investigated.…”
Section: Interventions To Improve Post-travel Readinessmentioning
confidence: 99%
“…Takahashi et al found total sleep time was significantly reduced on the second post-travel day following long-haul flight and elevated activity during sleep that persisted until the second post-travel day in 10 subjects travelling to destinations with 8–11 h time differences 61. Sleep loss is associated with sizeable effects on alertness,62 63 negative disturbances in mood, cognition and motivation and may have an affect on performance via these mechanisms 64–66.…”
Section: Effects Of Post-travel Sleep Deprivation On Performancementioning
confidence: 99%